Embedding Pancasila Values in Traditional Performance: The Role of Amaq Abir Theater in West Nusa Tenggara - Rapi Renda; Galih Suryadmaja; Mohamad Yudisa Putrajip; I Wayan Kusuma Di Biagi; Nurtikawati Nurtikawati; Dewi Puspita Ningsih; Muhammad Fazli Taib Saearani (Badan Pembinaan Ideologi Pancasila, 2026)
This study examines the role of Amaq abir traditional theatre in communicating ethical values associated with the principles of Pancasila within the Sasak community of West Nusa Tenggara, Indonesia. Preserved by Sanggar Pustaka Budaya in Central Lombok, Amaq abir represents an important form of local cultural heritage that conveys social and moral meanings beyond its artistic function. In the context of globalization, the growing influence of global culture has raised concerns regarding cultural continuity, identity formation, and shifts in moral values. This research employs a qualitative method with an ethnographic approach to explore how Pancasila-related values are articulated through traditional performance practices. Data were collected through participant observation, in-depth interviews with performers and community members, and documentation of rehearsals and performances. The findings indicate that Amaq abir performances communicate ethical values associated with the five principles of Pancasila through narrative dialogues, symbolic masks, traditional musical accompaniment, and collective participation. Values related to religiosity, humanity, unity, deliberation, and social responsibility are expressed both within the storyline and through the social interactions surrounding the performance. These findings suggest that traditional performing arts may function as culturally embedded spaces for character education and moral reflection within community life.